Discrimination in selection decisions: Integrating stereotype fit and interdependence theories - LEE, Sunyoung (Institutional Knowledge at Singapore Management University, 2015)
We integrate stereotype fit and interdependence theories to propose a model that explains how and why decision makers discriminate in selection decisions. Our model suggests that decision makers draw on stereotypes about members of different social groups to infer the degree to which candidates possess the specific ability required for the task. Decision makers perceive candidates that have a greater ability required for the task as less (more) instrumental to their personal outcomes if they expect to compete (cooperate) with the candidate, and they discriminate in favor of candidates that are perceived as more instrumental to them. We tested our theory in the context of racial (Studies 1-3) and age (Study 4) discrimination in selection decisions with all-male samples and found evidence consistent with our predictions. By explaining when and why decision makers discriminate in favor of, but also against, members of their own social group, this research may help to explain the mixed support for the dominant view that decision makers exhibit favoritism toward candidates that belong to the same social group. In addition, our research demonstrates the importance of considering the largely overlooked role of interdependent relationships within the organization in order to understand discrimination in organizations.